Diversidade de pequenos mamíferos em uma paisagem altamente fragmentada na Floresta Atlântica do sul do Brasil - Rodrigues, Daniele Pereira (2019)
Human activities have been causing high rates of destruction of natural habitats at an accelerated rate and reducing forest fragments, and this process affects the diversity and composition of animal species, resulting in local extinctions. In this context, the objective of this work was to evaluate the occurrence of non volant small mammal species in six fragments in the northern region of Rio Grande do Sul state and their relationship with the landscape metrics analyzed. The region is in a transition area between Deciduous Seasonal Forest and Mixed Ombrophilous Forest, a highly fragmented region of the Atlantic Forest biome. The analyzed fragments have an intermediate or advanced stage of regeneration, with a minimum size of 200x200m. To analyze small mammal communities, we established three transects with eight sampling points in each fragment, 10 meters apart, totaling 18 transects and 144 sampling points in the six fragments. At each sampling point, Tomahawk traps were placed in different strata (on the ground and understory). The sampling series consisted of 10 days per month of uninterrupted activity, and the traps were checked every morning. The study was conducted from July to December 2018, with a total sampling effort of 8,640 night traps. To compare the diversity among the six forest fragments, the Shannon Diversity Index (H ') was used. For each fragment analyzed the size, the central area and the shape index were determined using the software Fragstat. A multiple linear regression model was generated to verify the relationship between small mammal species and landscape metrics. 336 small mammals belonging to four species were captured: Akodon montensis, Oligorizomys nigripes, Sooretamys angouya and Gracilinanus microtarsus. There was a difference in species composition among the sampled fragments, where only two of the six fragments captured the four species. The species S. angouya was the only one that showed a significant positive correlation with the size (ha) metric and negative with the central area. Our results demonstrate that generalist species have a higher occurrence in forest fragments inserted in a highly agricultural landscape with low forest cover than specialist species. The degree of conservation of the fragments and the ecological attributes of each species reflects the low richness found. These results reinforce the importance of preserving small forest fragments in a predominantly agricultural matrix, as they are capable of maintaining remnant species of great ecological importance.